The Christmas stranger - Evans, Richard Paul (Gallery Books, 2025)
Three years after losing his family in a Christmas Eve accident, grieving Paul Wanless hasn't just given up on Christmas, he's given up on life. He can't imagine anything to keep him here--not his work as a computer repairman, not the residents in his Salt Lake City neighborhood, and certainly not the idea of connecting with someone new. When a stranger knocks on his door, claiming to be picking up a laptop, Paul allows him in--but discovers the man has a very different mission in mind. The mysterious stranger's name is Gabriel, and when Paul finds himself opening up to his visitor, Gabriel tells him, "I wouldn't do it, if I were you. It's not what you think." He then departs without another word. Paul brushes the experience aside as some trick of the imagination...until he crosses paths with a young widow and her bullied son, who've also received a visit from Gabriel. Has Gabriel brought new people into his life for a reason...but why? And who--or what--really is this Christmas stranger?